Brachial Approach As an Alternative Technique of Fibrin Sheath Removal for Implanted Venous Access Devices - Sotiriadis, Charalampos; Hajdu, Steven David; Doenz, Francesco; Qanadli, Salah D. (Frontiers in Surgery, 2017)
Implanted venous access device (IVAD) late dysfunction is commonly caused by fibrin sheath formation. The standard method of endovascular fibrin sheath removal is performed via the femoral vein. However, it is not always technically feasible and sometimes contraindicated. Moreover, approximately 4–6 h of bed rest is necessary after the procedure. In this article, we describe an alternative method of fibrin sheath removal using the brachial vein approach in a young woman receiving chemotherapy for breast cancer. The right basilic vein was punctured, and a long 6°F introducer sheath was advanced into the right subclavian vein. Endovascular maneuvers consisted on advancing Atrieve™ Vascular Snare 15–9 mm after catheter insertion in the superior vena cava through a 5.2°F Judkins left catheter. IVAD patency was restored without any complication, and the patient was discharged immediately after the procedure. In conclusion, fibrin sheath removal from an obstructed IVAD could be performed via the right brachial vein. Further research is necessary in order to prove efficacy of this technique.